Combining Case Study Research And Critical Reflection in Foreign/Second Language Methodology - Marjorie Hall Haley (Networks: An Online Journal for Teacher Research, 2001)
To date very little has been written about how foreign and second language teachers experience their pre-service teaching internships and the implications of these experiences on the quality of foreign and second language instruction in the US in K-12 settings. This article presents the case study of one student teacher intern involved in his 15-week experience in a linguistically and culturally diverse secondary school setting and how his case was used in a foreign/second language methodology course. It examines the extent and nature of the student's critical reflections in determining the basis of sound methodological and pedagogical approaches to second language instruction. Furthermore, it demonstrates the design and development of this case and the benefits of its use in one particular teacher education program. Additionally, this article will highlight, within the case study, the utilization of reflection and the creation of the professional development portfolio. Results indicated that students studying this case in the teacher education program discovered that they were able to link theory to practice and could understand and use educational theories and principles in becoming effective educators.